GLYCOME PECULIARITIES OF THE RAT MYOCARDIUM STRUCTURAL COMPONENTS UNDER EXPERIMENTAL MYOCARDIAL ISCHEMIA - Nadraga, B.A.; Strus, Kh.I.; Yashchenko, A.M.; Zhulkevych, I.V.; Lutsyk, A.D. (World of Medicine and Biology, 2019)
Using the routine histological methods and 8 lectin-peroxidase conjugates of different carbohydrate specificity (Con A, GNA, PNA, HPA, CNFA, WGA, SBA, LABA), the effect of experimental myocardial infarction on the morphological features and carbohydrate determinants of rat myocardium was studied. It was detected modification of carbohydrate determinants of myocardial structural components, especially in within endothelium of microcirculatory bed, formed elements of blood, which can be an important diagnostic marker of changes in adhesive properties and formation of blood clots. Lectin CNFA can be recommended for selective histochemical labeling of intercalated disks in between adjusting cardiomyocytes, and lectin WGA – as vascular endothelium marker in within rat myocardium. An increase in the number of macrophages identified by LABA lectin in affected myocardial tissues apparently indicates activation of the macrophage system induced by conditions of experimental myocardial infarction.